PENDAMPINGAN PENYUSUNAN MEDIA PEMBELAJARAN DARING BERBASIS DIGITAL BAGI KKG GUGUS 3 KECAMATAN HARJAMUKTI KOTA CIREBON - Erna Labudasari; Eliya Rochmah; Sri Sundhea Hastuti (Universitas Negeri Medan, 2022)
Distance learning activities require teachers to be more creative and skilled in using information technology media as online learning media to optimally develop the potential of elementary school students. However, based on initial observations, as many as 60% of elementary school teachers in 3 clusters of Harjamukti District, Cirebon City have never used a digital platform as an online learning medium due to limited ability and also not being familiar with the digital platform s Kahoot, Quizizz and Canva. As many as 90% of teachers are more familiar with WhatsApp group and zoom applications as online learning media. The objectives of PKM activities are: 1) Providing socialization on the use of digital platform s as learning media in elementary schools; 2) Provide Training and Assistance in the Use of Digital Platform s for Teachers. The method of implementing the activities uses the experiential learning method with the following stages of implementation: 1) Preparation, 2) the implementation of socialization of the use of digital platform s as learning media in elementary schools, 3) Implementation of training and assistance on the use of digital platform s for teachers, and 4) Implementation evaluation. The results of the activity show that: 1) The increase in teacher knowledge regarding the use of digital platform s as learning media in elementary schools by 95%, 2) Increased teacher skills in the use of digital platform s by 95%. Furthermore, the response of the activity participants showed that 67% of the participants gave a very good response while the remaining 33% gave a good response to the PKM activities.